Complement Set Reference after Implicitly Small Quantities: An Event-Related Potentials Study. Issue 2 (17th February 2018) - Ingram, Joanne; Ferguson, Heather J.
ABSTRACT: An anaphoric reference to the complement-set is a reference to the set that does not fulfil the predicate of the preceding sentence. Preferred reference to the complement-set has been found in eye movements when a character's implicit desire for a high amount has been denied using a negative emotion. We recorded event-related potentials to examine if, when a character's desire is denied with a negative emotion, the complement-set is immediately available for reference. Analysis of the N400 over posterior regions showed that although readers favored the reference-set after a positive emotion, there was no difference in responses between complement-set and reference-set references after a negative emotion. Processing of a complement-set reference did lead to an overall increase in negativity of the N400, suggesting that interpreting a complement-set reference incurred a general processing cost. This study provides novel data on the range of circumstances under which the complement-set is available.